New Patterns of World Mineral Development - Mikesell, Raymond Frech (London : British-North American Committee, 1979)
This report addresses the central problem of how adequate supplies of nonfuel minerals for the world economy can be assured over the remainder of this century. It brings out the complexities of modern mining projects and the reasons for the very large increases not only in costs but in lead times that have to be faced. In short, it discusses the patterns of mineral development that will be best serve the interests of all concerned and will be best adapted to the realities of the present situation.
Includes bibliographical references.
ne 28/03/2018
Loans
Keywords: Mines and Mineral Resources